Nicholas Kaldor and Kazimierz Łaski on the pitfalls of the European integration process - Michael A. Landesmann (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
Nicholas Kaldor and Kazimierz Łaski have been two very prominent exponents of Keynesian thinking. They both contributed to the debate on European economic integration, one (Nicholas Kaldor) in the early 1970s, when there were fierce debates about the United Kingdom's entry to the European Communities, and the other (Kazimierz Łaski) in the wake of the financial and economic crisis of 2008–2012, when the European Union and its Economic and Monetary Union were seriously challenged by potential disintegration. Both exponents provided deep and complementary inputs into an understanding of the centrifugal forces at work when a region with a rudimentary federal structure (but an extremely weak 'central state') embarks on tight economic integration with an inadequate macroeconomic policy framework in place.
Keywords: E12; E44; E60; E61; E65; F02; F15; F42; F43; F55; 330; European integration; macroeconomic imbalances; balance-of-payments constraints; EU and EMU reforms; Nicholas Kaldor; Kazimierz Łaski